(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
Consideration of multiperiod archaeological sites to understand the mechanisms of large-scale cultural changes is still a very rare research topic in Croatia. Technological traditions are of great importance, especially in the context of considering continuity, innovation, and change. In this paper, we used an archaeometric approach to investigate pottery technology. Therefore, this article presents an analysis of petrography and mineralogy of archaeological ceramics and potential raw materials collected in the vicinity of the multi-period archaeological site (the Neolithic through the Medieval period) Jagodnjak-Krčevine located in eastern Croatia, i.e. the south-western part of the Pannonian Basin. The primary goal is to determine what kind of clay recipe (clay and temper) potters used to make vessels in order to better understand their variability in the context of techno-functional features. The additional objective is to examine the availability and quality of clays for pottery production and to study their distribution in the local landscape. The analytical methods applied in the research are optical microscopy, X-ray diffraction, and grain size analysis. The comparison of archaeological ceramics with clayey materials established that ancient potters used locally available clays, and the selection of temper material added to the clay represents a strong element of techno-tradition, which is more pronounced for prehistoric communities. Furthermore, these results represent the first research in Croatia focused on a discussion about distances that potters travelled to obtain their resources in the different periods of the past, which can contribute to the study of a regional system of production and landscape use.